Press and Propaganda in The War of the Pacific: The Boletín de la Guerra (Arica - Tacna, December 1879 – May 1880) - Ibarra Cifuentes, Patricio Orlando (Revista de Historia Social y de las Mentalidades, 2023)
Peruvian soldiers stationed in the province of Moquegua of the ongoing conflict from the perspective of the army and the government of Nicolás de Piérola. In its 39 issues, this official propaganda medium used a discursive strategy to exhort to keep up the fight to value the leadership of Piérola as Head of State and of Rear Admiral Lizardo Montero in command of the Peruvian forces in Tacna and Arica. It also deployed an anti-Chilean rhetoric that served the interests of the Peruvian state and was in line with the majority opinion of the non-combatant population. From its review and analysis, evidence is obtained regarding the main characteristics of a newspaper conceived to inform a specific audience, which used the journalistic practices and tools of the last quarter of the 19th century, reporting from a geographic space where an essential part of the warlike operations of the confrontation for the saltpetre of Antofagasta and Tarapacá took place.